Relations between the Mamluk State and the Kingdom of Sicily (659AH-661AH/1260AD-1262AD) - حسن, غادة (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This study aims to examine the nature of the relations between the Mamluk state and the Kingdom of Sicily during the reign of Sultan Al-Zahir Baybars and Emperor Manfred Hohenstaufen, during a crucial period in the history of the two states. The Mamluk state was in the process of being established, and the Kingdom of Sicily was trying to preserve its existence and survival, and protect itself from external dangers. The research also seeks to identify the political and economic factors that contributed to the establishment of such relations, and to the role played by diplomacy in rapprochement and closer ties between the two countries, through the exchange of embassies, correspondence and gifts.